2020
DOI: 10.22146/buletinpsikologi.60212
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Reactance and Beliefs in Conspiracy Theories During the Covid-19 Pandemic: Overview of the Extended Parallel Process Model (EPPM)

Abstract: Compliance with health protocols plays an important role in minimizing the spread of Covid-19. However, Indonesia is still facing a robust challenge including non-compliance to persuasive recommendations or messages (psychological reactance) and belief in conspiracy theories. Issues related to conspiracy theories and theories had obscured the message for the people to keep their behavior safe from the virus. The Extended Parallel Process Model (EPPM) is a theory that explains how people would obey the messages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Similar findings were observed in a study by Freeman et al where 50% of adult participants in the UK expressed support for Covid-19 conspiracy-related beliefs [6]. The prevalence of Covid-19 conspiracy beliefs was also evident in various major cities in Indonesia, such as Surabaya (21%), Jakarta (18%), and Bogor (16.5%) [7].…”
Section: Introductionsupporting
confidence: 86%
“…Similar findings were observed in a study by Freeman et al where 50% of adult participants in the UK expressed support for Covid-19 conspiracy-related beliefs [6]. The prevalence of Covid-19 conspiracy beliefs was also evident in various major cities in Indonesia, such as Surabaya (21%), Jakarta (18%), and Bogor (16.5%) [7].…”
Section: Introductionsupporting
confidence: 86%
“…Indeed, pushing too strongly against people's beliefs can lead to psychological reactance, which is the perception that one's freedom to make choices or express one's beliefs are threatened (Steindl et al 2015). For instance, during the COVID-19 pandemic it was suggested that psychological reactance increased conspiracy belief and played a role in people's non-compliance with virus-mitigating behaviours (see Adiewna et al, 2020). We stress that these recommendations are intended to be applied to interactions in which persuasion and competitive debate are discouraged, and instead empathic understanding and accepting disagreements are preferred.…”
Section: Knowing When To Back Offmentioning
confidence: 99%
“…Psychological reactance plays an important role in compliance with the persuasive messaging regarding COVID-19 restrictions (Adiwena et al, 2020 ). With the announcement of the implementation of COVID-19 precautionary measures, people start developing emotions of anger which leads to psychological reactance and affects the intention of compliance (Krpan and Dolan, 2021 ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%